First person - Elia Escasany (The Company of Biologists, 2021)
First Person is a series of interviews with the first authors of a selection of papers published in Disease Models & Mechanisms, helping early-career researchers promote themselves alongside their papers. Elia Escasany is first author on ' Transforming growth factor β3 deficiency promotes defective lipid metabolism and fibrosis in murine kidney', published in DMM. Elia is a PhD student in the lab of Gema Medina-Gómez at Universidad Rey Juan Carlos, Madrid, Spain, investigating the role of TGFβ in renal fibrosis.